LncRNA as a regulator in the development of diabetic complications - Geng, Mengrou; Liu, Wei; Li, Jinjie; Yang, Ge; Tian, Yuan; Jiang, Xin; Xin, Ying (Frontiers in Endocrinology, 2024)
Diabetes is a metabolic disease characterized by hyperglycemia, which induces the production of AGEs, ROS, inflammatory cytokines, and growth factors, leading to the formation of vascular dysfunction and target organ damage, promoting the development of diabetic complications. Diabetic nephropathy, retinopathy, and cardiomyopathy are common complications of diabetes, which are major contributors to disability and death in people with diabetes. Long non-coding RNAs affect gene transcription, mRNA stability, and translation efficiency to influence gene expression for a variety of biological functions. Over the past decade, it has been demonstrated that dysregulated long non-coding RNAs are extensively engaged in the pathogenesis of many diseases, including diabetic complications. Thus, this review discusses the regulations of long non-coding RNAs on the primary pathogenesis of diabetic complications (oxidative stress, inflammation, fibrosis, and microvascular dysfunction), and some of these long non-coding RNAs may function as potential biomarkers or therapeutic targets for diabetic complications.